(untitled) (The International Journal for Scientific Research, 2026)
The study aimed to investigate the role of artificial intelligence technologies in enhancing the instructional methods used by teachers of students with autism spectrum disorder in primary schools in the Nazareth area. To achieve this aim, a simple random sample was drawn from the original population, consisting of 47 male and female teachers: 4 male teachers and 43 female teachers. A questionnaire was administered to them, designed according to a five-point Likert scale. Its items reflected the role of artificial intelligence technologies in enhancing instructional methods across four domains: (1) knowledge of the uses of artificial intelligence technologies, (2) the benefits of employing artificial intelligence technologies in enhancing instructional methods, (3) the difficulties faced by teachers in using artificial intelligence technologies, and (4) the importance of training in the use of artificial intelligence technologies for improving teachers’ performance and professional development. The study data were analyzed using the descriptive and analytical approaches. The most important findings were as follows: - The overall mean score of the study sample on the questionnaire, which reflected the role of artificial intelligence technologies in enhancing the instructional methods used by teachers of students with autism spectrum disorder in primary schools in the Nazareth area, was 3.32 out of 5 points, with a percentage of 66.4%, indicating a moderate level of estimation. - The mean scores of the four domains related to the role of artificial intelligence technologies in enhancing instructional methods were rated as high. However, the one-way analysis of variance for the repeated measure did not show statistically significant differences at the confidence level of α = 0.05 among these four domains. - The independent-samples t-test and the overall F-test did not show statistically significant differences regarding the role of artificial intelligence technologies in enhancing teachers’ instructional methods in primary schools in the Nazareth area attributable to gender, years of teaching experience, academic qualification, academic specialization, training courses in special education, or training courses in digital technology and artificial intelligence. The exception was the first domain, related to knowledge of artificial intelligence technologies and their uses, where differences were found attributable to years of teaching experience, in favor of teachers with 5 to 9 years of experience. The results also showed statistically significant differences in the first domain attributable to the number of training courses in digital technology and artificial intelligence, indicating that receiving training courses in this field contributes to raising teachers’ level of knowledge of artificial intelligence technologies and their uses. Accordingly, it can be said that the demographic and professional variables did not produce substantial differences in the total degree of the role of artificial intelligence technologies in enhancing instructional methods, except for some limited differences that appeared in the domain of knowledge of artificial intelligence technologies, which were associated with years of teaching experience and the number of training courses in digital technology and artificial intelligence. Based on these findings, the two researchers recommended conducting further future studies that link the theoretical and practical knowledge of teachers of students with autism spectrum disorder regarding the use of artificial intelligence technologies in enhancing instructional methods in primary schools in the Nazareth area.